Analisis Komunikasi Interpersonal Guru Dengan Murid Pada Pembelajaran Di Kelas 1 Madrasah Ibtidaiyah Al-Hidayah Bekasi - Zannabu Afifah; Dewi Utami (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Understanding interpersonal communication is not easy, especially when communicating with children under the age of 9, namely 1st grade elementary school students. Several teachers will encounter numerous challenges and obstacles in delivering teaching materials effectively to 1st grade students. This research aims to explore interpersonal communication between teachers and students in the learning process of first-grade Madrasah Ibtidaiyah Al-Hidayah Bekasi, as well as identifying inhibiting factors in interpersonal communication between teachers and students in the first-grade class. The study is conducted through a case study approach and employs qualitative research methods. The research findings indicate that interpersonal communication between teachers and first-grade students is effective. Teachers actively apply interpersonal communication in the classroom to enhance skills and assist students in understanding learning materials. However, hindering factors in the communication process include sender message barriers, receiver message barriers, and psychological barriers. Educators are required to be creative in presenting materials to prevent students from feeling bored and uninterested.